An Efficient Multi-Resolution Chain Coding - Andrej Nerat; Damjan Strnad; Krista Rizman Zalik; Borut Zalik (IEEE Access, 2024)
A new compact encoding is presented of rasterized bi-level shapes at multiple resolutions. The encoder accepts the Freeman chain code in four directions (F4) at the input, and builds a multi-resolution code named MrCC. The encoding process constructs the coarser representation of F4 chain code, and the resulting MrCC codes simultaneously. MrCC encodes the differences between sequences of F4 chain code from successive resolutions. Several transformations are performed during this process. Various rasterized shapes were used to analyse the efficiency of the new code, which was, on average, 22% better than the concatenation of F4 chain codes of various resolutions.